The Politics of Pandemic: Covid-Mitigating Response among 1st Time Mayors from Dynastic and Non-dynastic Families in the Philippines - Najarila, Mary Jane (Social Sciences and Development Review, 2023)
The study assessed the implementation of different mitigation programs imposed by the Inter-Agency Task Force (IATF) thru their guidelines and the initiatives spearheaded by first-time mayors with dynastic or non dynastic backgrounds during the surge of the pandemic. Similarly, variance analysis was conducted to determine whether there is a significant difference between the total number of COVID-19-positive cases, deaths, and recovery rates in their localities. Secondary data were collected from online news articles, government websites, and through the social media platforms of municipalities/cities, as well as the personal accounts of the mayors themselves. The following conclusions were made: There is no substantial causal relationship between the familial background of the mayor and the increase or decrease of COVID-19 cases in their respective localities; there is no significant difference in the implementation of programs imposed by the national government to the mayors with dynastic/non-dynastic backgrounds; and in terms of pandemic governance and leadership, it is crucial to think beyond the stereotypical beliefs related to political dynasties.